Mahalaga ako personal safety kit an exploration of the use of an educational kit on personal safety skills for the prevention of child sexual abuse to be used by parents educating children between ages 6-8 in Bagong Silang, Caloocan City - Gipa, Shellette
There is a presumption that children are vulnerable, passive, weak, and incapable and have diminished the capacity to survive on their own. This attitude tends to neglect and rob the rights of the children especially the sexually abused survivors to live, transform, and actualize to persons of great potential (Song, 2007). It is important for children at an early age to begin understanding that they have certain rights that other people should respect. These rights include the right to self-esteem and privacy, to resist other people's behaviors that are deemed uncomfortable and unwanted situations, to have assertiveness in telling about and to expect help from trusted adults when they experience violence or abuse from others. And the best way to prevent abuse is always education. Parents, as the children's first teachers, play a crucial role in the process of helping children participate for their own protection. They have the responsibility to prevent and teach their children about personal safety skills to avoid any form of abuse.